The Sun Vs The Guardian (Framing Berita The 1975 di Malaysia) - Evan, Evan; Yoedtadi, Moehammad Gafar (Koneksi, 2024)
The 1975 is a music group with an alternative rock or indie rock genre based in Manchester, England. In July 2023, the band The 1975 has just been involved in a case involving the vocalist of the band The 1975, Matty Healy, who violated the LGBT law in Malaysia. In this research, the author will analyze the news about the band The 1975 in two different media, namely The Sun media (Malaysia) and The Guardian media (England). This research aims to explain the framing of news about The 1975's appearance in Malaysia in The Sun and The Guardian media. This research uses several supporting theories, namely the reality theory of media construction, framing theory and journalism. This research uses a qualitative approach with the framing analysis method of Zhongdang Pan and Gerald M. Kosicki. Research data was obtained through analysis of subjects and objects based on theoretical foundations and previous research and supported by data validity techniques by journalism experts. The research results show that in fact the two media do not side with any particular person. However, there are differences in reporting in the two media, this is due to differences in background and ideology between the two media. The 1975 merupakan grup musik yang mempunyai genre rock alternatif atau indie rock yang berbasis di Manchester, Inggris. Pada bulan Juli 2023, Band The 1975 baru saja tersandung kasus yang dilakukan oleh vokalis Band The 1975 yaitu Matty Healy yang melanggar hukum LGBT di Malaysia. Pada penelitian kali ini, penulis menganalisis pemberitaan terhadap Band The 1975 pada dua media yang berbeda yaitu media The Sun (Malaysia) dan media The Guardian (Inggris). Penelitian ini bertujuan menjelaskan framing dari berita penampilan The 1975 di Malaysia pada media The Sun dan The Guardian. Penelitian ini menggunakan beberapa penunjang teori yaitu Teori Realitas Konstruksi Media, Teori Framing Media dan jurnalistik. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis framing milik Zhongdang Pan dan Gerald M. Kosicki. Data penelitian diperoleh melalui analisis terhadap subjek dan objek penelitian berdasarkan landasan teori dan penelitian terdahulu serta didukung dengan teknik keabsahan data oleh ahli jurnalistik. Hasil penelitian menunjukkan bahwa sebetulnya kedua media tersebut tidak memihak kepada suatu oknum tertentu. Tetapi adanya perbedaan pemberitaan pada dua media tersebut, hal itu dikarenakan adanya perbedaan latar belakang dan ideologi antara kedua media tersebut.